2000
DOI: 10.1063/1.480867
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical heterogeneity in nanoconfined poly(styrene) chains

Abstract: Fluids in nanoscopic confinements possess a variety of unusual properties, and in particular, remarkable dynamical heterogeneities which vary on length scales as short as a fraction of a nanometer. While the surface forces apparatus provides an experimental probe of macroscopic properties of fluids in contact with atomically smooth solid surfaces, few experimental probes are available which test the microscopic origins of these heterogeneities. In this article we describe our recent efforts to apply nuclear ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
100
0
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 40 publications
8
100
0
3
Order By: Relevance
“…Compared with other solid-state NMR techniques ( 1 H, 13 C), which were applied to polymers in PLS nanocomposites before, [15][16][17][18][19][20][21][22] 2 H NMR gives a more detailed picture of molecular motion. [10] To test for heterogeneity of the surfactant layer in OLS, we apply 31 P NMR on phosphonium surfactants.…”
Section: Full Papermentioning
confidence: 99%
“…Compared with other solid-state NMR techniques ( 1 H, 13 C), which were applied to polymers in PLS nanocomposites before, [15][16][17][18][19][20][21][22] 2 H NMR gives a more detailed picture of molecular motion. [10] To test for heterogeneity of the surfactant layer in OLS, we apply 31 P NMR on phosphonium surfactants.…”
Section: Full Papermentioning
confidence: 99%
“…It is critical to have many, independent, well-equilibrated initial configurations of the system to be simulated: as the polymer is held together by covalent bonds, the relaxation of the chain is determined by the slowest moving segments along the polymer. Even though mobile segments are expected to exist in large numbers [31], they will be bonded to portions of the polymer that remain "frozen" for timescales vastly longer than what is accessible by MD. Therefore, the only realistic way to explore a large portion of the configurational space is to start with many independent initial system conformations.…”
Section: Computational Detailsmentioning
confidence: 99%
“…It was concluded that cooperative relaxations of the intercalated polymer (i.e., totally confined) are weak and that confinement effectively prohibits bulklike crystallization. DSC and NMR studies of intercalated polystyrene (PS) also confirmed the absence of glassy relaxation [Krishnamoorti et al, 1996;Zax et al, 2000].…”
Section: Polymer/layered-silicate Nanocompositesmentioning
confidence: 84%